Curcumin Analogs Induce Apoptosis and G2/M Arrest In 4T1 Murine Triple-Negative Breast Cancer Cells - Retno Murwanti; Azmi Rahmadani; Ritmaleni Ritmaleni; Adam Hermawan; Bambang Sulistiyo Ari Sudarmanto (Indonesian Journal of Pharmacy, 2020)
Chemotherapy is the first-line treatment for triple-negative breast cancer (TNBC), yet toxicity and resistance effects have been the current problems. Curcumin,a natural compound, has been reported to exert anti-proliferative effects on various cancer cells, including breast carcinoma cells. However, the β-diketone moiety influences the stability of curcumin. Curcumin analogs, pentagamavunon-0 (PGV-0), and pentagamavunon-1 (PGV-1) were synthesized to improve the stability and activity of curcumin by modified the β-diketone moiety into mono-ketone pentanone. In this study, we evaluated the cytotoxicity, inhibition of cell cycle progression, and induction of apoptosis of curcumin and its analogs (PGV-0 and PGV-1) in murine triple-negative breast cancer 4T1 cell line. The cytotoxic evaluation was done by MTT assay, while apoptosis induction and cell cycle evaluation was performed by annexin V staining and detected by flow cytometry. Curcumin and its analogs, PGV-0, and  PGV-1, significantly inhibit the viability of 4T1 breast cancer cells with an IC50 value of 34.34µg/mL, 13.76µg/mL and 38.21μg/mL, respectively. Apoptosis analysis with a dose of 10µg/mL and 15µg/mL in 4T1 breast cancer cells showed that curcumin and its analogs effectively induce apoptotic in a dose-dependent manner. In cell cycle analysis using a dose of 15µg/mL, curcumin inhibited the cell cycle progression in the S phase, whereas PGV-0 and PGV-1 inhibited the cell cycle in the G2/M phase. It could be concluded that curcumin analogs, PGV-0 and PGV-1, have higher potential to be developed as anti-cancer agents by inducing cell cycle arrest and apoptosis in triple-negative breast cancer.